E-002 Development of a phantom that can mimic idiopathic intracranial hypertension and transverse sinus stenosis. (4th August 2020) - Valluru, K; Shen, T; O'Reilly, K; Haraldsson, H; Kao, E; Leach, J; Wright, A; Ballweber, M; Meisel, K; Saloner, D; Amans, M
Abstract : Purpose: Idiopathic Intracranial Hypertension (IIH) is a pathologic elevation of the intracranial pressure (ICP) with normal CSF composition which mostly affects younger women who are obese. IIH is most commonly presented along with focal stenosis of venous transverse sinus (TS). Venous sinus stenting (VSS) is an effective procedure that can resolve PT in patients with IIH and TS stenosis but has significant relapse rates. A benchtop phantom that can reliably mimic IIH pathophysiology and induce TS stenosis would allow evaluation of factors causing restenosis. Materials and Methods: Our benchtop phantom constitutes an interchangeable 3D printed TS flow model submerged in a rigid water-filled chamber akin to dura mater. The phantom is equipped with an underwater pressure sensor connected to a microcontroller and capable of continuously relaying the ICP values to a computer in real time. Two calibrated needle gauges connected externally on either side of the TS flow model monitor IVP gradient across the stenosis (figure 1A ). ICP is manipulated by infusing additional water analogous to increasing CSF, through the inlet provided on top of the phantom. To better approximate the compliance of the TS in vivo, we tested seven thin-walled flow models of same size made of four different materials with a range of shore hardness factors (27A – 60A). With glycerol-water mixture pumped through the model, the ICP was increased in the phantom from 0 – 60 cmH2 O in 5 cmH2 O increments and IVP gradient was recorded across the stenosis (n=3 trials per flow model). Measurements were obtained with the phantom positioned to resemble TS in both upright and supine positions respectively. Results: Among all the flow models tested, the model 3D printed with Agilus 30A was found to be a good surrogate for TS when the phantom was oriented in supine position. It produced a stenosis with a mean IVP gradient of 7.84 mmHg at a mean ICP of 25.5 cmH2 O, agreeing with typical lumbar puncture opening pressure values (>25 cmH2 O) seen in most IIH patients (figure 1B ). Conclusion: We developed a benchtop phantom that can mimic the pathophysiology of IIH and can reliably induce TS stenosis by increasing the ICP to the levels typically observed in patients. We anticipate that our phantom will facilitate evaluating anatomical and physiological parameters that induce restenosis and will eventually allow testing of new devices that could minimize VSS relapse rate in IIH patients. Disclosures: K. Valluru: None. T. Shen: None. K. O'Reilly: None. H. Haraldsson: None. E. Kao: None. J. Leach: None. A. Wright: None. M. Ballweber: None. K. Meisel: None. D. Saloner: None. M. Amans: 1; C; NIH R01 HL149124-01A1.